Digital Transformation of Minutes Preparation and Sessions Management through the Minutes Information System (SIRIH) of the Indonesian House of Representatives in 2025 - Imama, Muhamad Aaqil; Supriyatno, Budi; Hakim, Aziz (Dinasti Publisher, 2026)
The digital transformation of public institutions demands the integration of policy, governance, technology, and user behavior to generate public value. This qualitative study analyzes the implementation of the DPR RI Minutes Information System (SIRIH) at the DPR RI Secretariat General through a multi-level approach. At the macro level, the OECD Digital Government Policy Framework is used to assess digital governance maturity. At the meso level, a socio-technical system approach is used to analyze the integration of SPBE policies, organizational design, and court proceedings. At the micro level, the UTAUT model is used to explain the factors of system adoption and utilization by officials. Data were obtained through analysis of official documents and observation of work processes. The results show that at the macro level, SIRIH strengthens the efficiency, transparency, and accountability of court proceedings. At the meso level, SIRIH implementation encourages standardization of work processes and cross-unit coordination, but still faces limitations in system integration and alignment of technology design with organizational needs. At the micro level, performance expectancy and social influence are the main determinants of adoption, with challenges in digital literacy and interface quality. This study confirms that digital transformation of court proceedings is a multi-layered socio-technical process that requires simultaneous strengthening of policy, organizational design, and user capacity.